Computational modelling of concrete structures : proceedings of EURO-C 2014, St. Anton am Arlberg, Austria, 24-27 March 2014 /: proceedings of EURO-C 2014, St. Anton am Arlberg, Austria, 24-27 March 2014. ([2014]) - Bićanić, N (Nenad); Mang, H (Herbert), 1942-; Meschke, Günther
No abstract available